Selection Analysis of Secondary Pharmaceutical Industry Contract Manufacturers with Fuzzy Analytical Hierarchy Process (FAHP) Method - Saraswati, Mia; Kusumastuti, Ratih Dyah (International Journal of Economics Development Research (IJEDR), 2024)
This study aims to analyze the selection of contract manufacturer in secondary pharmaceutical industry using Fuzzy AHP. This study employs a quantitative approach using statistical analysis to assess the validity and reliability of the data then subsequently mapped into a matrix model. The Fuzzy AHP is applied to conquer the ambiguity and vagueness of personal knowledge. Six criteria were identified named quality, cost, service performance, compliance, delivery, and operational. The evaluation is conducted by a committee of five decision makers that include purchasing manager, toll manufacturing manager, production manager, quality assurance manager, and quality control manager of the industry. The results revealed that quality is the most important criteria in determining the selection of contract manufacturers in secondary pharmaceutical industry, followed by cost, compliance, delivery, operational and service performance. According to the results, contract manufacturer 2 was chosen to be the best to outsource operational activities of the industry. The results show that the proposed method could provide promising results in decision making process more appropriately. The proposed evaluation criteria provide a reference for pharmaceutical industry practices in the selection of contract manufacturers using Fuzzy AHP.